"AMERICA, YOU KNOW WHAT I'M TALKIN' ABOUT!": RACE, CLASS, AND GENDER IN BEULAH AND BERNIE MAC - Angela Nelson (Celt: A Journal of Culture, English Language Teaching & Literature, 2012)
This paper compares and contrasts The Beulah Show (ABC, 1950-1953) and The Bernie Mac Show (Fox, 2001-2006) in order to trace the differences and similarities between the racialized, gendered, and classed representations of blacks in American television situation comedy genre over a fifty-year period. The paper critically examines and interprets the image constructions of each series' central character, Beulah Brown and Bernie Mac, within the contexts of race, gender, and class, specifically utilizing Herman Gray's theory of the discursive practices of segregation ism, pluralism, and multiculturalism. The paper demonstrates that these image constructions are representative of race and black (objectivity and) subjectivity in US. society. The analysis of Beulah Brown is based on screenings of the episode "Donnie's Dance Date" which featured Hattie McDaniel, Ruby Dandridge, Ernest Whitman, David Bruce, Jane Frazee, and Stuffy Singer in 1951 and the analysis of Bernie Mac is based on screenings of "Bernie Mac, Ladies Man," the fourth episode of the series in 2001